Measurement of serum C-reactive protein levels in early second trimester as a predictor of preterm delivery - Senthil, Sujatha; Dhamayanthi, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preterm labour is the leading cause of perinatal morbidity and mortality. Infection plays a major role in preterm labour. Elevation of CRP, an inflammatory biomarker has been associated with spontaneous preterm birth. This study was aimed at evaluating the relation of C-reactive protein in early second trimester with preterm labour and neonatal morbidity. Methods: It is a prospective cohort study, 200 pregnant women of singleton pregnancy between the gestational age of 14 to 20 weeks were enrolled. After detailed history taking, maternal serum CRP levels were estimated by ELISA method. These women were divided into two groups according to CRP levels. Incidence of preterm delivery and incidence of neonatal morbidity was compared in both groups to ascertain if measured maternal CRP levels has any association with preterm labour and neonatal morbidity. Results: In this study 42 patients (21%) had preterm delivery. Of these 30 patients had CRP > 1.5mg/dl; 12 had CRP < 1.5 mg/dl. In CRP increased group, 30 patients (57.7%) delivered preterm, 22 patients (42.3%) had term. It was found that increased levels of maternal serum CRP in early pregnancy were associated with increased incidence of preterm delivery. According to this study if the CRP value 1.5 the sensitivity will be 71.4% and specificity will be 86% to predict the preterm. Of the total 42 preterm babies, 1 from Group A (8.3%) and 12 from Group B (40%) developed sepsis. So increased CRP has association with neonatal sepsis. Conclusions: Elevated maternal serum CRP concentration in early second trimester was associated with increased incidence of preterm delivery and showed a positive correlation with neonatal sepsis.